Analisis Perbandingan Kinerja Keuangan Perusahaan Transportasi Sebelum dan Selama Pandemi Covid-19 - Rossi Okta Kurniawati; Agus sucipto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Covid-19 pandemic, which has been endemic throughout the world, is no exception in Indonesia since the beginning of 2020 until now, it has had many impacts in various fields, especially the economy. The Central Statistics Agency (BPS) noted that Indonesia's economy in the second quarter contracted by 5.32%, this condition was caused by declining growth in various businesses. This study aims to compare the financial performance of transportation companies using financial ratio analysis before and during the Covid-19 pandemic for transportation companies listed on the Indonesia Stock Exchange in 2018-2021 so that it can be a recommendation if you want to buy transportation company shares. This research is a quantitative research. In this study data collection from the Indonesia Stock Exchange (IDX) is in the form of secondary data through the official website of the Indonesia Stock Exchange in the form of financial reports. For a total sample of 15 transportation companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period, the sampling technique was purposive sampling. The data analysis technique used in this study was the normality test, Paired Sample T-Test, and Wilcoxon Signed Rank Test. The results showed that the condition of transportation companies before and during the Covid-19 pandemic using profitability ratios with ROA, ROE and NPM measurements did not differ before and during the Covid-19 pandemic, using liquidity ratios with CR measurements there were no differences before and during the Covid pandemic -19, and using the solvency ratio with DER and DAR measurements there is also no difference before and during the Covid-19 pandemic.